Fermat's last theorem: from fermat to wiles (1995)
The solution to Fermat's Last Theorem was announced by Wiles (Cambridge, June 23, 1993) as a consequence of his proof of the Shimura- Taniyama- Weil conjecture for semi-stable elliptic curves.